EFFECT OF SUPPLEMENTATION OF CONCRALS, GnRH AND PGF2alpha ON POSTPARTUM REPRODUCTION IN BUFFALOES - PATEL, P P; PANCHAL, M T; PATEL, B N; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
A total of 107 advance pregnant buffaloes were studied for their postpartum fertility. Among thebuffaloes studied, the incidences of anoestrus and sub-oestrus were found to be 15.74 and 15.74 percent, respectively. The mean days of calving to first postpartum oestrus (FPPE) and service period fortreatment groups: T-I (Concentrate and minerals supplementation), T-11 (GnRH), T-111 (PG) and IV (Control)group were found to be 52.70±1.85 (47.25 to 58.15), 76.18±3.14 (66.84 to 85.52), 62.94± 0.29 (range53.60 to 72.28) and 115.96 ±7.25 (107.93 to 123.99), and 60.26±2.75 (53.62 to 66.89), 91.00±6.25(85.86to 109.34), 88.90±7.94 (range 74.52to 103.28)and 112.24±2.75(101.20to 123.26), respectively,both parameters differing significantly (p
Keywords: Postpartum anoestrus; Service period; Concentrates; Minerals; Buffaloes